Siblings' voices: A prospective investigation of experiences with a dying child. Issue 3 (16th March 2018) - Eaton Russell, Ceilidh; Widger, Kimberley; Beaune, Laura; Neville, Alexandra; Cadell, Susan; Steele, Rose; Rapoport, Adam; Rugg, Maria; Barrera, Maru
ABSTRACT: Sibling relationships reflect a unique childhood bond, thus the impact on a sibling when a child is seriously ill or dying is profound. We conducted a prospective, longitudinal, qualitative study over 2 years using interpretive descriptive methodology to understand siblings' perspectives when a brother or sister was dying at home or in hospital. The insights from the 10 siblings revealed complex experiences, both personal and with the ill child, their families, and peers. These experiences were paradoxically sources of strain and of support, revealing the importance of validation and normalization in assisting siblings to successfully navigate the experience.